Pemahaman Mahasiswa Terkait Materi Mata Kuliah Pendidikan Pancasila dalam Menghadapi Era Society 5.0 - Supriyono, Supriyono; Nugraha, Dadi Mulyadi; Supriatna, Aang; Adha, Muhammad Mona (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze student understanding regarding the material for the Pancasila Education course. This study used a quantitative approach with a descriptive type to analyze students’ level of understanding. The study results showed that as many as 76.6 percent of students had understood the legal basis of the Pancasila Education course. As many as 86.3 percent of students had understood the civilizing of Pancasila values during the New Order era. As many as 91.8 percent of students understood the basic Indonesian state law as the rule of law. Students with a percentage of 86.9 percent understood the concept of staatsfundamentalnorm, 75.1 percent of students understood Pancasila as the source of all sources of law, 72.6 percent of students understood the concept of Pancasila as a juridical source, and 81.5 percent of students understood the juridical sources of Pancasila as a philosophical system. As many as 41 percent of students understood the concept of Pancasila as the basis of the state, 57.8 percent of students got the juridical sources of Pancasila as the basis of the state correctly, and 88.8 percent of students understood Pancasila as the imperative of the state.